Collaboration Strategies with Micro-Influencers: Building Trust Through Community - Bahriyah, Euis Nurul (PT. Anagata Sembagi Education, 2025)
This study aims to examine the government's crisis communication strategy in dealing with misinformation in the digital era, focusing on the effectiveness of collaboration with micro-influencers in building public trust through a community approach. The method used is Systematic Literature Review (SLR), which allows the systematic identification, evaluation, and synthesis of scientific literature. The literature search process is carried out through databases such as Scopus, ScienceDirect, Google Scholar, and ProQuest using relevant keywords. The inclusion criteria include publications in the last five years (2020–2024), written in English or Indonesian, and contain empirical data related to micro-influencers, audience trust, and community collaboration strategies. From the selection process, as many as 10 selected scientific articles were analyzed thematically to identify patterns of collaboration, community approaches, and trust-forming factors. The results of the study show that an effective crisis communication strategy must be adaptive, transparent, and collaborative, and involve digital actors such as micro-influencers who have closeness to the community. This collaboration has been proven to be able to strengthen the delivery of validated information and build public trust. The study recommends reforming the government's public communication policy to be more responsive to digital dynamics, placing trust and public engagement as the main foundation in dealing with the information crisis.